THE EFFECTS OF TEACHING MEDIA AND GRAMMAR MASTERY TOWARDS STUDENTS’ SPEAKING SKILL AT STATE JUNIOR HIGH SCHOOLS IN TANGERANG BANTEN - Fiza Asri Fauziah Habibah (Pujangga: Jurnal Bahasa dan Sastra, 2018)
ABSTRACTThe research aims to know the effect of teaching media and grammar mastery towards students‘ speaking skill. This research was conducted at State Junior High Schools Cisauk Tangerang Banten with 574 population and the sample was 60 students which was gained through simple random sampling. This research is a kind of ex-periment method which means to give the different treatments upon two students‘ learning groups. The collec-tion of the data is done by giving multiple choice test. The gain data was then analyzed by using descriptive analysis. The research findings show that there is a significant effect of teaching media towards students‘ speaking skill at State Junior High Schools Cisauk in Tangerang Banten, there is a significant effect of grammar mastery towards students‘ speaking skill at State Junior High Schools Cisauk in Tangerang Banten, and there are significant interactive effects of teaching media and grammar mastery towards students‘ speaking skill at State Junior High Schools Cisauk in Tangerang Banten. Therefore, it can be recommended that the teachers should provide teaching media in teaching speaking skill and the students should have a good grammar mastery to have a good speaking skill.Keywords: Teaching Media, Grammar Mastery, Speaking SkillABSTRAKPenelitian ini bertujuan untuk mengetahui pengaruh media pembelajaran dan penguasaan tata bahasa terhadap kemampuan berbicara siswa. Penelitian ini dilaksanakan di sekolah Sekolah Menengah Pertama di Cisau, Tan-gerang, Banten dengan jumlah populasi sebanyak 574 orang siswa dan sampel sebanyak 60 orang siswa yang didapat dari teknik random sampling. Penelitian ini menggunakan metode eksperimen yaitu memberikan perla-kuan berbeda terhadap dua kelompok siswa. Pengumpulan data dilakukan dengan memberikan tes pilihan gan-da. Data yang didapat kemudian dianalisis menggunakan descriptive analysis. Hasil penelitian menunjukkan adanya pengaruh media pembelajaran terhadap kemampuan berbicara siswa di SMPN Cisau, Tangerang, Ban-ten, terdapat pengaruh penguasaan tata bahasa terhadap kemampuan berbicara siswadi SMPN Cisauk, Tange-rang, Banten, dan terdapat pengaruh interaktif yang signifikan media pembelajaran dan penguasaan tata bahasa terhadap kemampuan berbicara sisw di SMPN Cisauk, Tangerang, Banten. Oleh karena itu, para guru dianjur-kan untuk menyediakan media pembelajaran dalam pengajaran berbicara dan para siswa hendaknya menguasai tata bahasa yang baik agar mempunyai keterampilan berbicara yang baik.Kata Kunci: pengaruh media, penguasaan tata Bahasa, kemampuan berbicara